Comparison between Dry, MQL, and Cryogenic Cooling Technique on Surface Integrity of Burnished Surface - Rachmat, Haris; Mahalil, Khairuddin; Rahim, Erween Abd; Mohid, Zazuli (International Journal of Integrated Engineering, 2019)
Environmental concerns has contributed towards higher demands for green products. Therefore, various machining conditions, such as dry and near dry machining have been introduced to resolve the cutting fluid problem. However, the application of cryogenic cooling still not well understood especially for burnishing process. It is essential to initiate a study on the effect of cryogenic cooling technique to substitute other techniques to improvement burnishing process. Carbon dioxide is used as the cryogenic gas under supercritical state, and compare with dry and minimal quantity lubricant. Solid carbide burnishing tool is used with a diameter and corner radius of 16 mm and 1 mm, respectively. The result shows that burnishing process under cryogenic condition recorded less burn mark and better tool wear than dry and MQL conditions. In addition, cryogenic condition exhibits significant grain refinement and surface hardness. In conclusion, the performance of carbon dioxide gas under supercritical state outperformed other coolant conditions.